Tertiary evolution of the western Tarim basin, northwest China: A tectono‐sedimentary response to northward indentation of the Pamir salient. Issue 3 (6th June 2013) - Wei, Hong‐Hong; Meng, Qing‐Ren; Ding, Lin; Li, Zhen‐Yu
ABSTRACT: [1] This paper deals with the Tertiary tectonic and sedimentary evolution of the western Tarim basin based on an integrated stratigraphic, sedimentary, structural, and tectonic analyses. Basin evolution is divided into three stages: Paleogene, Miocene, and Pliocene. The western Tarim basin was the easternmost part of the Tethyan realm from Late Cretaceous to Paleogene, and marine sedimentation continued into the Early Miocene. Miocene development of the western Tarim basin was chiefly governed by West Kunlun right‐slip faulting and the simultaneous northward thrusting of the Pamir salient and Tianshuihai terrane. Yecheng subbasin developed as a pull‐apart basin owing to synchronous activity of the West Kunlun and the Shache‐Yangdaman right‐slip faults. Hotan foreland basin formed in response to northward displacement of the Tianshuihai terrane, and another might have developed in front of the advancing Pamir salient in the Miocene. Basinward thrusting became predominant in the orogenic belts adjacent to the western Tarim basin in the Pliocene. North‐directed displacement and uplift of the Tiklik thrust terrane fragmented the preexisting Hotan foreland basin, and collision of the Pamir with the southern Tian Shan deformational fronts caused complete destruction of the Miocene Pamir foreland basin. Eastward displacement of the Qimugen fold‐thrust system led to flexural subsidence of the Yecheng subbasin in the Pliocene. Kashi subbasin developed as part of the southern Tian Shan foreland basin, and was controlled by the eastern Pamir as well. A tectonic scenario is proposed to illustrate complicated interplay of the western Tarim basin with its peripheral orogens in the Tertiary. Key Points: The western Tarim basin was not a simple foreland basin in the Tertiary Basin subsidence and sedimentation were governed by peripheral orogens Pamir indentation led to changes of basin types of the western Tarim